2021
DOI: 10.1152/japplphysiol.00401.2020
|View full text |Cite
|
Sign up to set email alerts
|

Neuromechanical adaptations of foot function to changes in surface stiffness during hopping

Abstract: Humans choose work-minimizing movement strategies when interacting with compliant surfaces. Our ankles are credited with stiffening our lower limbs and maintaining the excursion of our body's center of mass on a range of surface stiffnesses. We may also be able to stiffen our feet through an active contribution from our plantar intrinsic muscles (PIMs) on such surfaces. However, traditional modelling of the ankle joint has masked this contribution. We compared foot and ankle mechanics and muscle activation on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…While the ankle contributed much of the increase in positive work performed in the Damped condition, the intrinsic foot muscles were able to contribute significant portion of this work (25% of that performed at the ankle). That the foot can contribute to replace energy dissipated by a damped surface is a novel finding and when considered with the other recent work from our group (13,14,17,18,23,25), further highlights the versatility of our feet in the control of movement.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…While the ankle contributed much of the increase in positive work performed in the Damped condition, the intrinsic foot muscles were able to contribute significant portion of this work (25% of that performed at the ankle). That the foot can contribute to replace energy dissipated by a damped surface is a novel finding and when considered with the other recent work from our group (13,14,17,18,23,25), further highlights the versatility of our feet in the control of movement.…”
Section: Discussionmentioning
confidence: 65%
“…However, we uncovered in prior work that running in cushioned shoes with a viscoelastic midsole leads to an increase in intrinsic foot muscle activation, compared with barefoot running ( 19 ). When considered with our recent findings that footwork and muscle activation decrease when hopping on an elastic surface ( 14 ), we propose that feet may also play an important role in how humans adjust to operating on surfaces that dissipate energy.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Through the combined efforts of its passive and active components, the foot is capable of transitioning between compliant spring, energy producing motor and energy absorbing damper during tasks with different work requirements at the centre of mass (Birch et al, 2021;Riddick et al, 2019;Smith et al, 2021). To determine how feet with different morphologies behave during such different tasks, participants were asked to walk and run (Froude number = 0.25 and 1.00, respectively) at three inclinations each (walking: -20, 0, 20%; running: -10, 0, 10%) on a force-sensing, fore-aft, tandem treadmill (AMTI, USA).…”
Section: Treadmill Walking and Runningmentioning
confidence: 99%
“…As Lauder (1995) argues, function is not defined by musculoskeletal structure itself, but by how it is used, i.e., "the motor programs in the central nervous system". There is ample evidence for this argument in relation to the foot, as various investigations have shown that the neuromuscular control of intrinsic and extrinsic foot muscles plays an important role in the mechanical function and versatility of the foot (Birch et al, 2021;Kessler et al, 2020;Riddick et al, 2019;Smith et al, 2021). Thus, future investigations examining the link between foot form and function might benefit from also examining the potential link to the neuromuscular control of relevant muscles during various locomotor tasks.…”
Section: General Implications Of the Statistical Shape-function Modelmentioning
confidence: 99%